Evaluation of contemporary echocardiographic and histomorphology parameters in predicting mortality in patients with endomyocardial biopsy-proven cardiac AL amyloidosis - Koutroumpakis, Efstratios; Niku, Adam; Black, Christopher K.; Ali, Abdelrahman; Sadaf, Humaira; Song, Juhee; Palaskas, Nicolas; Iliescu, Cezar; Durand, Jean-Bernard; Yusuf, Syed Wamique; Lee, Hans C.; Buja, L. Maximilian; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction: This study examined the role of echocardiographic and cardiac histomorphology parameters in predicting mortality in patients with cardiac AL amyloidosis. Methods: Patients with endomyocardial biopsy-proven cardiac AL amyloidosis treated at MD Anderson Cancer Center between 6/2011 and 6/2020 were identified. Stored echocardiographic images and endomyocardial biopsy samples were processed for myocardial strain analysis and a detailed histomorphology characterization. Results: Of 43 patients; 44% were women and 63% white. Median age was 65 years; 51% underwent stem cell transplantation (SCT). Thirty patients (70%) died during follow up (median follow up: 4.1 years). Lower LA strain (<13.5%) and absence of SCT as a time-varying covariate were significantly associated with increased risk of death in the multivariate cox regression analysis. Higher LV mass and lower RV tricuspid annular plane systolic excursion were associated with increased odds of having ≥5% interstitial amyloid deposition on biopsy in the multivariate logistic regression analysis. Conclusions: Lower LA strain independently predicted mortality in our cohort, and its performance in the routine assessment of AL amyloidosis may be beneficial. Furthermore, SCT for cardiac AL amyloidosis was associated with improved OS. These findings need to be confirmed by larger studies in the era of contemporary systemic therapies.